Relationship between forage neutral detergent fiber and non-fibrous carbohydrates on ruminal fermentation products and neutral detergent fiber digestibility in goats - Pinho, Ricardo M. A.; Santos, Edson M.; de Oliveira, Juliana S.; de Carvalho, Gleidson G. P.; Alves, Joyce P.; Macêdo, Alberto J. da S.; Pereira, Gildenia A.; Pereira, Danilo M.; Perazzo, Alexandre F.; Zanine, Anderson de M. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: There is a comprehensive understanding of the role of dietary fiber as a nutrient and its function during digestion in cattle. On the other hand, the role of fiber digestion in goats has not received similar attention. Objective: To evaluate the effects of different ratios of forage neutral detergent fiber (fNDF) and non-fibrous carbohydrates (NFC) on ruminal fermentation products, and in vitro neutral detergent fiber (NDF) digestibility in goats. Methods: A 3 × 5 factorial arrangement in a completely randomized design with three fNDF levels (100, 190, and 290 g/kg) and five NFC levels (350, 400, 450, 500, and 550 g/kg) was used. The experiment was performed in vitro. Two ruminally fistulated goats were used as rumen liquid donors. Results: The ratios between fNDF and NFC affected all ruminal parameters (p<0.05). Increasing NFC levels in diets containing 100 and 290 g/kgfNDF resulted in linear increase (p<0.05) in ammonia concentration after 48 h fermentation. There was no adjustment of linear models (p>0.05) for pH values. Total volatile fatty acids (VFA) and their individual molar proportions were affected (p<0.05) at all fNDF and NFC levels. The NDF digestibility was not affected (p>0.05) by fNDF or NFC levels, except for diets containing 290 g/kg fNDF, which were fit to a quadratic model (p<0.05). Conclusion: The relationship between fNDF and NFC concentrations affect the fermentation end products and in vitro NDF digestibility. NFC plays a more consistent role than fNDF in the ruminal microbial ecosystem of goats during in vitro fermentation.